Mini-Review: The Contribution of Adipokines to Joint Inflammation in Inflammatory Rheumatic Diseases - Toussirot, Eric (Frontiers in Endocrinology, 2020)
Inflammatory rheumatic diseases (IRD) are complex disorders characterized by chronic inflammation of the joints and related skeletal structures. The most common forms of IRD are rheumatoid arthritis (RA) and spondyloarthritis (SpA), including axial SpA (axSpA) and psoriatic arthritis (PsA). Obesity is a frequent comorbidity in RA and PsA, and to a lesser extend in axial SpA. The association between obesity and IRD may be explained by the release from fat tissue of several bioactive proteins, namely adipokines. Adipokines are involved in the regulation of various processes such as lipid or glucose metabolism, but also inflammation. Adipokines are interrelated with the immune system, with both innate and adaptive immune cell connections. Several adipokines with pro-inflammatory effects have been identified such as leptin, visfatin or resistin. Conversely, adiponectin and more specifically its low molecular weight isoform, is considered to have antiinflammatory properties. In this review, we discuss the contribution of adipokines to the joint inflammation of IRD, the relation they have with immune pathways of these diseases, their links with the structural impact on peripheral joints and/or axial skeleton, and also the influence they may have on the cardiometabolic risk of IRD.